STATUS MAKRO INVERTEBRATA PADA PERAIRAN DAS CITARUM HULU YANG TERCEMAR - Wage Komarawidjaja (Jurnal Teknologi Lingkungan, 2005)
Macro invertebrate study in Upper Citarum Watershed conducted for a fewtarget, such as understanding some organisms indices and the function in aquatic ecosystem.In this study, besides identified macro invertebrate type also measured some water quality parameter that influence to the exchange of its habitat quality. Water quality laboratory analysis indicates that pressure to macro invertebrate life happened due to the change in environmental quality Upper Citarum Watershed, either by physical impact (erosion) and also chemical impact (domestic, industries and agriculture). To overcome the problem mentioned, environmental monitoring enhancement to be needed, so that calamity of aquatic organism losses can be avoided.